PERTUMBUHAN BIBIT TANAMAN KOPI ARABICA (Coffea arabica,L) PADA BERBAGAI DOSIS KOMPOS KULIT GELONDONG KOPI DAN SP-36 - Khadijah, Khadijah; Hairunnas, Hairunnas; Tilawarni, Beti (Cangkok, 2021)
"Growth of Arabica Coffee Seeds (Coffea arabica L.) At Various Doses of Coffee Lob Skin Compost and SP-36" The purpose of this study was to determine the effect of giving coffee bark compost, to determine the effect of SP-36 fertilizer, to determine the effect of giving bark compost. SP-36 fertilizer coffee on the growth of arabica coffee plant seeds. This research was conducted in the experimental garden of the Faculty of Agriculture, Gajah Putih University in Blang Bebangka Pegasing, Central Aceh. The research was carried out from August to November 2017, with an altitude of 1200 m above sea level, having a pH of 6.5. This study aims to determine the effect of giving coffee bark compost, to determine the effect of SP36 fertilizer on the growth of coffee seedlings, to determine the effect of giving coffee bark compost and SP-36 fertilizer to the growth of Arabica coffee seedlings. The treatment of coffee log skin compost and SP-36 fertilizer had a significant effect on coffee plant height at the age of 30, 60 and 90 days after planting. The stem diameter at the age of 30, 60 and 90 days after planting had a significant effect, while the number of leaves at 90 days after planting had no significant effect.